Sosialisasi Pelayanan Publik di Desa Mekarjaya Kecamatan Cimarga dalam Penyaluran Bantuan Program Keluarga Harapan (PKH) - Eli Apud Saepudin; Luis Fiska Rahayu; Ita Rosita Wahyiah (Yayasan Perguruan Kampus, 2024)
This service aims to evaluate the effectiveness of public service socialisation in the distribution of Family Hope Program (PKH) assistance in Mekarjaya Village, Cimarga District. PKH is a conditional social assistance programme that aims to improve the standard of living of poor and vulnerable families. The research method used is a descriptive method with a qualitative approach. Data were obtained through in-depth interviews, participatory observation, and documentation. The results showed that the socialisation conducted by the village government together with PKH Facilitators has gone well, although there are still some obstacles such as limited human resources and a lack of community understanding of the mechanism and objectives of PKH. Active community participation in socialisation is very important to ensure that the distribution of assistance is right on target and to minimise errors in the administrative process. In conclusion, the socialisation of public services in Mekarjaya Village in the distribution of PKH assistance is quite effective, but there is a need for improvement in terms of community understanding and strengthening the capacity of PKH facilitators. Recommendations include increasing the frequency of socialisation, additional training for PKH facilitators, and using more diverse media to convey information to the community.